Analogues of 2-Deoxyglucose as inhibitor candidates for hexokinase II identified via virtual screening analyses - Tanbin, Suriyea; Ogu Salim, Nurhainis; Ahmad Fuad, Fazia Adyani (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Dengue fever is one of the major global health issues, yet specific treatment remains vague. The human hexokinase isoform II (HK2) is one of the crucial enzyme for dengue virus (DENV) replication and thus has been suggested as a potential therapeutic target for DENV drug development. In this paper, compounds with potential HK2 inhibitory activity have been identified by using a combination of ligand-based and structurebased virtual screening approaches. In the initial ligand-based approach, a known HK2 inhibitor, 2- Deoxyglucose (2-DG) was used as the query molecule, which resulted in the identification of analogues of 2-DG with scores ranging from 0.739-0.763. The analogues were docked against the crystal structure of HK2 (PDB ID: 2NZT) in complex with alpha-D-glucose (GLC) and beta-D-glucose-6-phosphate (BG6) by using Auto Dock 4 programme, on chain B where the active sites were located. The docking hits exhibited binding energy ranging from -7.63 to -4.98kcal/mol. Six top-ranked compounds which are most similar to 2-DG were subsequently analysed based on their predicted binding affinity with the catalytic residues (Thr620, Lys621, Asn656, Lys618, Asp657, Phe604, Asn735, Glu629, Gly710, Gly622 and Glu708), H bond analysis and toxicity effect. Among the selected top six compounds, only compound 4 (ZINC26898487) is non-toxicant and has shown good binding energy (-7.63 kcal/mol) relative to 2-DG and contains four H bonds; two with Lys621, one with Glu629 and another one with is Thr620. Meanwhile, the binding energy of 2-DG itself is -7.40kcal/mol when in complex with HK2, with two H bonds; one with Lys621 and another one with Glu708. In this drug design computational studies, compound 4 (ZINC26898487) is suggested to have potentials to inhibit HK2 activity relative to the known inhibitor (2-DG), thus pave the way towards the discovery of new dengue therapeutics